1995
DOI: 10.1111/j.1570-7458.1995.tb01931.x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐enhanced essential oils as mosquito larvicides

Abstract: Using laboratory bioassays with fourth‐instar Culex pipiens form molestus larvae, we explored the larvicidal properties of two representative plant‐derived oils, eucalyptus oil and turpentine (two grades), and cineole, the main component of eucalyptus oil. Each was larvicidal alone, but efficacy was enhanced when the spreading pressure was increased by adding 1% insoluble surfactant (Arosurf MSF) plus 1% detergent. Cheap turpentine was more effective than more refined turpentine. These mixtures were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The abnormal and irregular movement of larvae was also observed by Choochote et al (2004) treated with Apium graveolens. Corbet et al (1995) noted the susceptibility of mosquito larvae and pupae to surface materials entering the trachea. Our results are in agreement with those reported by Chaithong et al (2006) and Islam et al (2003) against C. quinquefasciatus.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal and irregular movement of larvae was also observed by Choochote et al (2004) treated with Apium graveolens. Corbet et al (1995) noted the susceptibility of mosquito larvae and pupae to surface materials entering the trachea. Our results are in agreement with those reported by Chaithong et al (2006) and Islam et al (2003) against C. quinquefasciatus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tripathi et al (2002) studied that C. longa leaf oil possesses toxic, antifeedant, oviposition-deterrent and ovicidal activity against Rhyzopertha dominica F. (lesser grain borer), Sitophilus oryzae L. (rice weevil) and Tribolium castaneum Herbst (red flour beetle). The larvicidal mode of action of essential oils was investigated by Corbet et al (1995) who distinguished the susceptibility of mosquito larvae and pupae to surface materials entering their tracheal system, observing that essential oils increased the tendency to tracheal flooding and chemical toxicity. An assessment of the results presented here with the result from various other studies on the efficacy of different essential oil products is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mode of action of tested materials was not studied. The larvicidal mode of action of essential oils was previously investigated by Corbet et al (1995); WHO observed that essential oils increase the tendency of tracheal flooding and chemical toxicity in mosquito larvae. Usta et al (2002) demonstrated that isolated pure compounds interfered with proton transfer in the mitochondria leading to larval mortality.…”
Section: Discussionmentioning
confidence: 99%